MOTIVATION ET ASSIDUITÃ‰ AU TRAVAIL CHEZ DES FONCTIONNAIRES DU TRÃ‰SOR PUBLIC IVOIRIEN - GACHA, Franck-Gautier (European Scientific Journal, ESJ, 2015)
The article aims at showing the relationship between the factors of motivation and assiduity of the Public Treasury agents at work. It covers 35 civil servants from the Human Resources Department and General Services. We have used the global motivation scale (EMG-28) to collect the data necessary for the analysis. The results show that civil servants from the Public Treasury are punctual and invest themselves in their work in order to achieve the objectives which are set for them. These behaviors are correlated with the factors of motivation such as quarterly bonuses and liability in the work. The study reveals that the more the civil servant is motivated, the more he is assiduous at work. In other words, the intrinsic motivation and the extrinsic motivation influence either assiduity at work of Public Treasury civil servants. The exploitation of this article could lead to redefine the management policy of human resources as currently practiced in the Ivorian public administration in order to lead it towards service quality and performance as desired by users